THE PRINCIPAL’S LEADERSHIP AS THE EFFORT TO BUILD STUDENTS’ CHARACTER - Ipong Dekawati (International Journal of Educational Management and Innovation, 2020)
Education is an effort to change behavior as well as building the character of the students. The decisive character of students is the foundation for the realization of national dignity in the future. In the education institution, the principal has the responsibility for making an effort to build the students’ character. This research focused on investigating the principal’s leadership in building students’ character. The research method used is descriptive and verification methods—a quantitative method conducted in this research. The data collection, the direct observation within five junior high schools, interviews with five principals of junior high school, and questionnaire (closed and structured) distributed to 85 teachers. The samples determined by using Slovin formulas with a simple random sampling technique. The regression analysis technique used in the process of data analysis. The significant test was done by doing F-test. The result shows that principal leadership is one of the alternative ways to build students’ character. Based on the result, the author suggests that (1) the principal improves information disclosure through communication by maximizing digital communication facilities and holding flag ceremony to convey information optimally. (2) The principal builds solid teamwork and participates in social activities through cooperation with local communities in protecting the environment.